Misoprostol Inhibits Lipopolysaccharide-Induced Pro-inflammatory Cytokine Production by Equine Leukocytes - Martin, Emily Medlin; Messenger, Kristen M.; Sheats, Mary Katherine; Jones, Samuel L. (Frontiers in Veterinary Science, 2017)
Pro-inflammatory cytokines including TNF, IL-1, IL-6, and IL-8 are potent immune mediators that exacerbate multiple equine diseases such as sepsis and laminitis. Unfortunately, safe and effective cytokine-targeting therapies are lacking in horses; therefore, novel mechanisms of inhibiting cytokine production are critically needed. One potential mechanism for inhibiting cytokine synthesis is elevation of intracellular cyclic AMP (cAMP). In human leukocytes, intracellular cAMP production is induced by activation of E-prostanoid (EP) receptors 2 and 4. These receptors can be targeted by the EP2/4 agonist and prostaglandin E1 analog, misoprostol. Misoprostol is currently used as a gastroprotectant in horses, but has not been evaluated as a cytokine-targeting therapeutic. Thus, we hypothesized that misoprostol treatment would inhibit pro-inflammatory cytokine production by lipopolysaccharide (LPS)-stimulated equine leukocytes in an in vitro inflammation model. To test this hypothesis, equine leukocyte-rich plasma (LRP) was collected from 12 healthy adult horses and used to model LPS-mediated inflammatory signaling. LRP was treated with varying concentrations of misoprostol either prior to (pre-treated) or following (post-treated) LPS stimulation. LRP supernatants were assayed for 23 cytokines using an equine-specific multiplex bead immunoassay. Leukocytes were isolated from LRP, and leukocyte mRNA levels of four important cytokines were evaluated via RT-PCR. Statistical differences between treatments were determined using One-Way RM-ANOVA (Holm-Sidak post-hoc testing), or Friedman’s RM ANOVA on Ranks (SNK post-hoc testing), where appropriate (p <0.05, n = 3-6 horses). These studies revealed that misoprostol pre- and post-treatment inhibited LPS-induced TNF and IL-6 protein production in equine leukocytes, but had no effect on IL-8 protein. Interestingly, misoprostol pre-treatment enhanced IL-1 protein synthesis following 6 hours of LPS stimulation, while misoprostol post-treatment inhibited IL-1 protein production after 24 hours of LPS stimulation. At the mRNA level, misoprostol pre- and post-treatment inhibited LPS-induced TNF, IL-1, and IL-6 mRNA production, but did not affect IL-8 mRNA. These results indicate that misoprostol exerts anti-inflammatory effects on equine leukocytes when applied before or after a pro-inflammatory stimulus. However, the effects we observed were cytokine-specific and sometimes differed at the mRNA and protein levels. Further studies are warranted to establish the inhibitory effects of misoprostol on equine cytokine production in vivo.